Application of Channel and Content Youtube Learning Media to Volleyball Skill Learning Outcomes - Aryana Tri Andyani; Carsiwan; Salman (Universitas Negeri Semarang, 2026)
This study aims to determine the influence and effectiveness of the application of CCY (YouTube Channel and Content) learning media on the learning outcomes of volleyball skills of grade VIII students in the subject of Physical Education at Junior high school 1 Pasirjambu. This study uses a quasi-experimental method with a quantitative approach involving two groups, namely the experimental class that is given treatment using CCY learning media and the control class that uses conventional learning. The research instrument is a volleyball basic technique skill test which includes bottom passing, top passing, and bottom serve, referring to the NCSU Volleyball Skills Test Battery Volleyball Skills Test Battery. Data analysis was carried out through the Kolmogorov–Smirnov normality test, Levene homogeneity test, independent sample t-test, N-Gain test, and covariate analysis (ANCOVA) with the help of the IBM SPSS application. The results of the study showed that the data was distributed normally and homogeneously. Independent sample t-tests showed significant differences between the learning outcomes of volleyball skills of students in the experimental class and the control class (p < 0.05). The results of the N-Gain test showed a higher increase in learning outcomes in the experimental class with the medium to high improvement category, compared to the control class in the low to medium category. ANCOVA's analysis strengthens the finding that the application of CCY learning media has a significant effect on improving students' volleyball skills after being controlled by initial grades. The conclusion of this study is that CCY learning media is effective and has a positive effect in improving students' volleyball skill learning achievements. This media can be used as an innovative alternative in Physical Education learning to optimally improve students' motivation, movement understanding, and skills.